Bio-economy at the crossroads of sustainable development - Vargas-Hernández, José G.; Pallagst, Karina; Hammer, Patricia (Ibero-american JournalL of Bioeconomy and Climate Change e-ISSN 2410-7980, 2018)
This study aims to review, analyze and systematize the knowledge created on bio-economy to develop a conceptual and theoretical framework based on the transdisciplinary study of biology and socioeconomy to be used in further research. It begins from the questioning of what are the benefits that bio-economy has compared to the neoclassical economy. The methods employed is the critical analytic, descriptive, deductive-inductive and suggests a holistic and transdisciplinary approaches. As a result, the core of the study presents the principles under which this new scientific paradigm in sustainable development can continue creating more scientific knowledge to be used in the formulation and implementation of strategic choices for the bio production, bio distribution and bio consumption process.